106k views
4 votes
Answer these In scientific notation with work shown, adding scientific notation.

9.9 x 10^-1 + 5.2 x 10^-2

3.24 x 10^5 + 8.3 x 10^1

1.24 x 10^0 + 5 x 10^-1

User Zetawars
by
6.6k points

1 Answer

5 votes

Answer:

1.
9.9 * 10^(-1)   + 5.2 * 10^(-2) = 104.2 * 10^(-2)

2.
3.24 * 10^(5)   + 8.3 * 10^(1) =32408.3 * 10^(1)

3.
1.24 * 10^(0)   + 5 * 10^(-1) = 13.64 * 10^(-1)

Explanation:

1)
9.9 * 10^(-1)   + 5.2 * 10^(-2)

Now,
9.9 * 10^(-1) =
99 * 10^(-2)

So,
99 * 10^(-2)   + 5.2 * 10^(-2) =
104.2 * 10^(-2)

2.
3.24 * 10^(5)   + 8.3 * 10^(1)

Now,
3.24 * 10^(5) =
32400 * 10^(1)

So,
32400 * 10^(1) + 8.3 * 10^(1) =
32408.3 * 10^(1)

3.
1.24 * 10^(0)   + 5 * 10^(-1)

Now,
1.24 * 10^(0) =
12.4 * 10^(1-)

So,
1.24 * 10^(0)  + 12.4 * 10^(1-) =
13.64 * 10^(-1)

User Grzegorz Krukowski
by
6.1k points